INDEKS PELESTARIAN FUNGSI LINGKUNGAN HIDUP (IPLH): SARANA ALTERNATIF UNTUK MENILAI KINERJA PENGELOLAAN LINGKUNGAN PERKOTAAN - Pamekas, Pamekas (Jurnal Gea, 2006)
Evaluating the performance of the urban environmental management in Indonesia is not easy task due to the fact that there is no standard measure that can be utilities for evaluation. The parameters that are employed in urban environmental management are not often complete and sometimes apply to a certain sector only. Clean urban program (Adipura) and clean river program (Prokasih) are the example of this sectoral approach which is not justifiable and impressive result. However, attempts should be made to find a workable way to support decision making processes. This research uses a deterministic dynamics approach to model the dynamic performance of urban environmental management for the town of Majalaya. Results indicates that the urban environmental management program for the town of Majalaya has achieved high degree of performance. However, most other town in Bandung regency are generally need further improvement. Three methods that have been used to study their dynamic behavior may be used to measure the improvement of the urban environment management program.Â Key word: Performance, Urban Environmental management.